Generational difference in media consumption during the COVID-19 pandemic - Sanje, G.; Çarboğa, O.S. (Nova Science Publishers, Inc., 2021)
It is well known that the COVID-19 pandemic has substantially increased the amount and frequency of media consumption, both in traditional and digital spaces. Individuals access several media sources on different devices for information, entertainment, and socializing purposes. Although media consumption increased during the COVID-19 pandemic, each generation consumed media differently, with different device preferences and usage percentages. These differences between generations are important, especially for media content providers, marketers, and businesses. This chapter investigates media consumption and device usage with secondary data, analyzing generational similarities and differences and predicting possible implications, especially for media content providers and marketers in the "new normal. " © 2021 Nova Science Publishers, Inc.
Keywords: Covıd-19; Generational Differences; Media Consumption